Reestructuración técnico administrativa de la empresa Alimentos Cañaveral de la ciudad de Bogotá (2017)
The present document was made in the premises of the company Alimentos Cañaveral in the year 2016, with the general objective of making a technical and administrative restructuring in which the first part was an internal and external diagnostic was made to determine the current situation of the company and its environment making use of different tools like a PESTAL analysis and the DOFA matrix.